Nominal Group Systems and Structures in Lhasa Tibetan. Issue 3 (3rd July 2021) - Wang, Pin
Abstract : This paper presents a text-based study of the construal of entities through nominal groups in Lhasa Tibetan based on a focus text selected from a local folk tale. It approaches the grammatical description of nominal group systems and structures from ideational and textual perspectives, taking as point of departure the discourse semantic systems of ideation and identification . From the perspective of ideation, nominal groups construe entities that realize items in field, which are classified or composed, with or without associated properties. From the perspective of identification, nominal groups either present or presume the identity of entities in discourse. In terms of nominal group grammatical functions, the nucleus of a Lhasa Tibetan nominal group is a Thing, which enters into multivariate structure with post-Thing functions including Classifier, Epithet, Quantity, Perspective, Deictic and Function Marking, and pre-Thing functions Qualifier and Embedding Marking. In terms of word classes realizing these functions, Lhasa Tibetan nominal groups involve nouns, pronouns, adjectives, numerals, quantifiers, determiners and clitics. The description also deals with complexing and embedding.